The relevance of foreign experience in countering criminal offenses in the customs sphere - Delechuk, Andriy (Actual problems of law (Aktual'ni problemi pravoznavstva), 2024)
The article is devoted to consideration of the foreign experience in combating corruption both in general and criminal offenses in the customs sector, in particular.  Since the deductive method of scientific cognition is chosen, the publication outlines the criminological experience of combating corruption inherent in each legal system as a whole, with further specification of anti-corruption measures specifically in relation to provision of customs services.The publication provides data on organization of anti-corruption, including in the customs sector, in the countries of the European Community, both those, which have a sustainable development of anti-corruption measures (Germany, France, UK and Italy) and in the states, which are adapting their legal framework within the political association of the European Community and are intensively working to reduce corruption risks and the negative impact of corruption as such on the order of public relations (Romania and the Baltic states). Special attention is paid to the Scandinavian trends in combating corruption, and the article notes that the Asian experience (Singapore and South Korea) is relevant, reflecting the reality of fundamental changes and criminological possibilities for reducing corruption figures. At the same time, the author suggests that foreign experience is useful provided that it is relevant, i.e., adequate to the conditions, in which it will be implemented. The author concludes that a globally effective method of combating corruption in any public sphere is transparency, i.e. transparency of the state policy on organization of administrative service delivery by public authorities. In other words, it refers to the state of transparency in the exercise of power. In particular, the actual implementation of this concept implies publicity and openness in the personnel policy in selection of customs officials, publicity of information on anti-corruption investigations, making public of property data, etc. Along with this, development of the codes of ethics and a corresponding corporate “zero tolerance” for corruption is also important.In addition, the study states that the international community is effectively using technological advances in anti-corruption measures. Specifically, it refers to the electronic format of most customs services. In author’s opinion, artificial intelligence, which, despite the available shortcomings in its work, is capable to objectify bureaucratic processes in the customs authorities, can also provide qualitative results in combating corruption in the customs sector.